Development of a photocatalytic zirconia-titania ultrafiltration membrane with anti-fouling and self-cleaning properties. Issue 6 (December 2021) - Bortot Coelho, Fabrício Eduardo; Deemter, Dennis; Candelario, Victor M.; Boffa, Vittorio; Malato, Sixto; Magnacca, Giuliana
Abstract: A photocatalytic Ce-Y-ZrO2 /TiO2 ultrafiltration membrane was successfully prepared on a ZrO2 /SiC support by a modified sol-gel process. The top active layer is 2 µm thick, uniform and defect-free. The membrane presented a molecular weight cut-off (MWCO) of 19 kDa (equivalent to a pore size of 6 nm) and a high pure water permeability, 160 Lm −2 h −1 bar −1 . The high hydrophilicity and negative surface charge of the membrane favoured its great retention of proteins (bovine serum albumin, whey protein, and hemoglobin), indigo dye, and humic acid. The membrane was effective in photodegrading phenol and humic acid under simulated sun light irradiation. During humic acid filtration tests, the membrane presented better anti-fouling properties (smaller flux decline) and higher permeate flux under irradiation compared to the filtration in the dark. Moreover, self-cleaning properties were observed by irradiating the membrane, which enabled recovering up to 97% of the original flux. Consequently, a longer operation without chemical cleaning is possible, reducing costs and the process footprint. Further investigation would allow the development of innovative treatments for dinking and wastewaters by combining filtration and advanced oxidation processes for the abatement of contaminants of emerging concern in the presence of natural organic matter. Graphical abstract: ga1 Highlights: First photocatalytic membrane on a SiC support. High water permeability (160 L m −2 h −1 bar −1 ) for its pore size (6 nm). High retentions of humic acid, indigo dye, and proteins. Photocatalytic activity in the degradation of phenol and humic acid. Anti-fouling and self-cleaning properties under sunlight irradiation.